PERUMUSAN STRATEGI PENGEMBANGAN BUDIDAYA IKAN BANDENG (Chanos-chanos) DIKELURAHAN SAMATARING MELALUI ANALISIS SWOT DAN QSPM - Fauzi, Latifah Asmaul; Raisa, Daeva Mubarika; Megawati, Megawati (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2025)
This study aims to determine the strategy and alternative strategies for developing sustainable milkfish (Chanos chanos) cultivation in Samataring Village, East Sinjai District, Sinjai Regency. The research method used is a quantitative descriptive approach, with analysis using the Internal Factor Evaluation Matrix (IFE), External Factor Evaluation Matrix (EFE), and Quantitative Strategic Planning Matrix (QSPM). Based on the results of the analysis, the IFE Matrix shows that the internal factors of milkfish cultivation in Samataring Village are in the moderate category. This indicates a combination of strengths that can be utilized and weaknesses that need to be addressed. Meanwhile, the EFE Matrix analysis revealed that external factors are in the strong category. This indicates that the external environment offers many prospective opportunities, although there are still threats that need to be watched out for. Furthermore, the results of the QSPM Matrix analysis of six alternative strategies obtained from the SWOT Matrix indicate that the most recommended alternative strategy is to utilize farmer experience and natural resources to increase the scale and quality of production to meet high market demand and expand market access. This strategy has the highest Total Attractive Score (TAS) value, which is 6.46, compared to other alternative strategies. Therefore, this strategy is the main priority for the development of milkfish cultivation at the research location.